2017
DOI: 10.18632/oncotarget.15485
|View full text |Cite
|
Sign up to set email alerts
|

The urokinase plasminogen activation system in gastroesophageal cancer: A systematic review and meta-analysis

Abstract: BackgroundThe urokinase plasminogen activation (uPA) system is a crucial pathway for tumour invasion and establishment of metastasis. Although there is good evidence that uPA system expression is a clinically relevant biomarker in some solid tumours, its role in gastroesophageal cancer is uncertain.ResultsWe identified 22 studies encompassing 1966 patients which fulfilled the inclusion criteria. uPA, uPAR, or PAI-1 expression is significantly associated with high risk clinicopathological features. High uPA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 46 publications
(62 reference statements)
1
49
1
7
Order By: Relevance
“…A systematic review of nine studies reported a pooled expression of 25% (146 of 573 patients) for HER-2 in EAC, but this meta-analysis revealed large differences in results between studies [19]. The pooled expression of uPAR was reported as 57% (range 14-90) for 12 gastroesophageal cancer studies [20], which is considerably higher than the 15% in our results. This may be explained by the random selection of tumor tissue.…”
Section: Discussioncontrasting
confidence: 84%
“…A systematic review of nine studies reported a pooled expression of 25% (146 of 573 patients) for HER-2 in EAC, but this meta-analysis revealed large differences in results between studies [19]. The pooled expression of uPAR was reported as 57% (range 14-90) for 12 gastroesophageal cancer studies [20], which is considerably higher than the 15% in our results. This may be explained by the random selection of tumor tissue.…”
Section: Discussioncontrasting
confidence: 84%
“…Another key gene "PLAU" gene located on 10q22.2 encodes urokinase type plasminogen activator (uPA), transforming plasminogen into plasminogen. 29 And previous studies have shown that uPA protein is mainly located in the cytoplasm, and both ectopic and eutopic endometrium express uPA protein, 30 which is positively expressed in vascular endothelial cells. 31 It is involved in the occurrence and development of endometriosis.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it plays an important role in cancer progression and metastasis. In addition, expression pattern, secretion, and function of uPA members have been observed in a broad range of human malignancies [6,7]. A number of investigations have indicated that uPA, uPAR, and PAI-1 are elevated in hepatocellular carcinoma (HCC) in comparison to normal liver tissues [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it plays an important role in cancer progression and metastasis. In addition, expression pattern, secretion, and function of uPA members have been observed in a broad range of human malignancies [6,7].…”
Section: Introductionmentioning
confidence: 99%